Revolt of the saints : memory and redemption in the twilight of Brazilian racial democracy - Collins, John F., 1965 April 19- (Duke University Press, 2015)
Anthropologist John F. Collins explores shifts in racial identification in Brazil by examining the transformation of a celebrated Afro-Brazilian neighborhood in Salvador, Brazil from a red light district into an idealized UNESCO World Heritage Site, wherein its residents were celebrated yet stigmatized and expelled.